The Effect of Depression and Cognitive Impairment on Enrollment in Medicare Part D - Zivin, Kara (2009)
OBJECTIVES: To examine concerns that vulnerable populations, such as depressed or cognitively impaired beneficiaries would have challenges accessing Part D coverage. DESIGN: Logistic regression analysis was used to assess whether elderly Medicare beneficiaries with depression or cognitive impairment differentially planned to and actually signed up for Part D. SETTING: 2004 and 2006 data from the Health and Retirement Study (HRS) were used, including a subsample that completed the Prescription Drug Study (PDS) in 2005. PARTICIPANTS: Nine thousand five hundred ninety-three HRS respondents and 3,567 PDS respondents. MEASUREMENTS: The outcome variables of interest were planned and actual enrollment in Part D. The independent variables were depression and cognitive impairment status. The analyses were adjusted using clinical and demographic predictors including age, sex, race or ethnicity, educational attainment, net worth, marital status, health status, number of health conditions being treated with prescription medications, and presence of a caregiver. RESULTS: Although having depression or cognitive impairment was associated with a higher likelihood of planning to and actually signing up for Part D in unadjusted analyses, in adjusted analyses, having depression or cognitive impairment was not significantly associated with whether Medicare beneficiaries planned to enroll in or actually enrolled in Part D. CONCLUSION: Vulnerable Medicare beneficiaries with depression or cognitive impairment were able to access Part D benefits to the same extent as nonvulnerable beneficiaries. More research is needed to determine how well Part D meets the needs of these populations.